Biomass production and morpho-phsysiological effects on sunflower plants (Helianthus annuss L.) under induced magnetic fiels (2023)
One of the major concerns at a global level relies on the influence that global warming has had and will continue having and therefore climate change on different economic sectors, mainly in developing countries, which are more vulnerable and with less resilience in their population. Nowadays, it is evident the global trend of searching different sources of raw material with potential to be used for biomass production. Considering this issue, this project analyzed the effect produced by the magnetic fields induced on plants Helianthus annuss L, as an enhancer of biomass production, as well as the morpho-physiological variations presented. Exposure of seeds to different intensities of magnetic fields (intensity of 14 µT and 422 µt) was: 1, 3 and 5 hours a day for 15 days, permanent exposure for 15 days, using as a witness seeds without exposing. Planting was carried out in 24 cm3 sockets with coconut fiber previously disinfected and moisturized as substrate. The planting trays were placed in semi-controlled growth zone to a light intensity of 3,000 lux with 12h light cycles at a temperature of 23 ° C and an average relative humidity of 43%. The variables studied are percent germination, growth dynamics, number of roots, production of fresh mass and dry biomass, chlorophyll content a, b and total as well as carotenoids. Physiologically the relative growth rate, net assimilation rate, leaf area index, crop growth rate, absolute growth rate, duration of leaf area and specific leaf area were determined. A simple analysis of variance (ANOVA) between the average of the samples per treatment was performed with a significance level of 95% (a = 0.05) in order to establish if there are significant differences for the variables in evaluation. In the case of not existing meaningful differences among the samples, a multiple range test was performed using the statistical package Statgraphics Centurion. The best results were obtained in seeds treated with permanent magnetic fields with intensity of 14 µT seeds, which demonstrated a significant increase in the value of most indicators studied, being more evident in germination percentage, stem length, number of roots, accumulation of fresh and dry mass as well as chlorophyll. An increased level of chlorophylls gives an indirect measure of the high potential that these plants have to produce biomass. © Copyright 2017, AIDIC Servizi S.r.l.